The Influence of Variation of Charcoal Husk Ratio in Andosol Plant Media to Growth and Production of White Corn Biomass (Zea mays cv anoman) - Hutauruk - Nim: 11414031 , Sulastri
Rapid population growth causes the current agricultural system to increase the production rate of its nutritional sources, especially carbohydrate content. But not all regions have the ideal land for rice production. This study aims to determine the effect of soil cropping media composition andosol and charcoal husk on soil physical properties and productivity of white corn crops and determine the optimal composition of husk husk: andosol. The composition of planting media used as the treatment in this study was andosol soil as control, soil mixture andosol with 90:10 husk husk; mixture of andosol soil with 70:30 husk charcoal: a mixture of andosol soil with 50:50 husk charcoal and a mixture of andosol soil with 30:70 husk charcoal with vermicompost and a compound ponksa 15:15:15. Parameters observed in maize included plant height, root dry weight, green forage and corn while the planting medium parameters included C: N ratio, fill weight, porosity, moisture content, mineral and soil organic. The results showed that the productivity of dry weight of white corn on soil andosol soil medium 100%, andosol: chamber comparison 90:10; 70:30; 50:50; and 30:70 respectively are 2.59 tons / ha, 3.49 tons / ha, 2.40 tons / ha, 5.36 tons / ha and 4.15 tons / ha respectively. The composition of planting medium that gives the most optimum result is the composition of planting medium of soil mixture of andosol with a 30:70 husk coals with an average height of 149 cm; dry white corn weight of 134 grams; forage dry weight of 42.4 grams; and dry root weight of 45.59 grams.